Free space optical communications with distributed switch‐and‐stay combining. Issue 6 (27th March 2018) - Gupta, Juhi; Dwivedi, Vivek K.; Karwal, Vikram; Ansari, Imran Shafique; Karagiannidis, George K.
Abstract : The authors study the performance of an amplify‐and‐forward dual‐hop, switch‐and‐stay combining receiver, used in free space optical communications over non‐identical fading channels. One path is characterised by the generalised Málaga (or M distribution), whereas the other is influenced by the combined effects of Gamma–Gamma distributed atmospheric turbulence, pointing error and path loss. Novel closed‐form expressions for the end‐to‐end moment generating function, probability density function, and cumulative distribution function are derived in terms of Meijer's G function. Furthermore, the performance of the system is analysed, and closed‐form expressions are presented for the end‐to‐end outage probability and channel capacity.